ASSESSMENT OF AWARENESS AND UTILIZATION OF FAMILY PLANNING METHODS AMONG ELIGIBLE COUPLES OF RURAL FILED PRACTICE AREA, KORWAR, KALABURAGI - CHANDRASHEKHAR; SANTOSH BIRADAR; VINOD S KAMBLE; PRATIBHA RAO K (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study was conducted to assess the awareness about the family planning methods and to estimate the utilization of various family planning methods among rural population in Korwar, Kalaburagi. Methods: This was a community based cross-sectional study conducted in Korwar, a rural field practice area of ESIC Medical College, Kalaburagi district, Karnataka. The data were collected from 210 eligible couples using predesigned semi-structured questionnaire by house-to-house visit. The data collected were entered in MS Excel and analyzed using Statistical Package for the Social Sciences software. Results: The majority (80%) of the men and women were aware about family planning methods in our study and its utilization was 75.2%. There was a significant association between gender, education, number of living children, and awareness of family planning methods, whereas association between religion, education, and utilization of methods was found to be statistically significant. Conclusion: Although the awareness regarding family planning is on positive side there is definitely hesitancy noted for the utilization of the same. Awareness activities and practices should be promoted at individual and family level in the community.